2023
DOI: 10.1128/spectrum.04385-22
|View full text |Cite
|
Sign up to set email alerts
|

A New Potential Resource in the Fight against Candida auris: the Cinnamomum zeylanicum Essential Oil in Synergy with Antifungal Drug

Abstract: This study highlights how small doses of CZ-EO are able to inhibit the secretion of fluconazole and promote its accumulation in the fungal cell. In this manner, the drug is able to exert its pharmacological effects bypassing the resistance of the yeast. If further studies will confirm this synergy, it will be possible to develop new therapeutic formulations active in the fight against C. auris resistances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
(54 reference statements)
1
6
0
Order By: Relevance
“…The MFC values obtained with EO are comparable to those obtained with CIN alone. This demonstrates, as known by previous works, that the main component of this phytocomplex is responsible for antifungal properties [18][19][20]. EOs and their active components are generally characterized by some drawbacks such as high volatility, chemical instability, and low solubility in water, hence their limited use in medical therapy [21,22].…”
Section: Discussionsupporting
confidence: 75%
“…The MFC values obtained with EO are comparable to those obtained with CIN alone. This demonstrates, as known by previous works, that the main component of this phytocomplex is responsible for antifungal properties [18][19][20]. EOs and their active components are generally characterized by some drawbacks such as high volatility, chemical instability, and low solubility in water, hence their limited use in medical therapy [21,22].…”
Section: Discussionsupporting
confidence: 75%
“…The results indicated that Cinnamomum zeylanicum essential oil was most effective against C. auris (MIC; 0.06% v/v) in synergy with antifungal drug fluconazole. Further they verified that cinnamaldehyde was the sole reason for the antifungal activity [52]. In the same year, another group of researchers identified the antifungal potency of Cinnamomum cassia essential oil [53], this oil also rich in chemical constitute like cinnamaldehyde [54].…”
Section: Essential Oils Are the Potential Sources Of Novel Antifungal...mentioning
confidence: 94%
“…The results indicated that Cinnamomum zeylanicum essential oil was most effective against C. auris (MIC; 0.06% v / v ) in synergy with the antifungal drug fluconazole. Further they verified that cinnamaldehyde was the sole reason for the antifungal activity [ 58 ]. In the same year, another group of researchers identified the antifungal potency of Cinnamomum cassia essential oil [ 59 ], this oil also being rich in chemical compounds like cinnamaldehyde [ 60 ].…”
Section: Therapeutic Optionsmentioning
confidence: 99%